Polar solvent fluctuations drive proton transfer in hydrogen bonded complexes of carboxylic acid with pyridines: NMR, IR and ab initio MD study. Issue 2 (12th December 2016) - Koeppe, B.; Pylaeva, S. A.; Allolio, C.; Sebastiani, D.; Nibbering, E. T. J.; Denisov, G. S.; Limbach, H.-H.; Tolstoy, P. M.
Abstract : Dual bands in IR spectra show that an ensemble of short-living solvatomers creates a dual-maximum distribution of proton positions in a series of strongly OHN-bonded complexes of chloroacetic acid with nitrogen bases in CD2 Cl2 . Abstract : We study a series of intermolecular hydrogen-bonded 1 : 1 complexes formed by chloroacetic acid with 19 substituted pyridines and one aliphatic amine dissolved in CD2 Cl2 at low temperature by 1 H and 13 C NMR and FTIR spectroscopy. The hydrogen bond geometries in these complexes vary from molecular (O–H⋯N) to zwitterionic (O − ⋯H–N + ) ones, while NMR spectra show the formation of short strong hydrogen bonds in intermediate cases. Analysis of CO stretching and asymmetric CO2 − stretching bands in FTIR spectra reveal the presence of proton tautomerism. On the basis of these data, we construct the overall proton transfer pathway. In addition to that, we also study by use of ab initio molecular dynamics the complex formed by chloroacetic acid with 2-methylpyridine, surrounded by 71 CD2 Cl2 molecules, revealing a dual-maximum distribution of hydrogen bond geometries in solution. The analysis of the calculated trajectory shows that the proton jumps between molecular and zwitterionic forms are indeed driven by dipole–dipole solvent–solute interactions, but the primary cause of the jumps is the formation/breaking of weak CH⋯O bonds from solvent molecules to oxygen atoms of the carboxylate group.